2005
DOI: 10.4049/jimmunol.174.12.8200
|View full text |Cite
|
Sign up to set email alerts
|

Human BDCA-1-Positive Blood Dendritic Cells Differentiate into Phenotypically Distinct Immature and Mature Populations in the Absence of Exogenous Maturational Stimuli: Differentiation Failure in HIV Infection

Abstract: Current immunological opinion holds that myeloid dendritic cell (mDC) precursors migrate from the blood to the tissues, where they differentiate into immature dermal- and Langerhans-type dendritic cells (DC). Tissue DC require appropriate signals from pathogens or inflammatory cytokines to mature and migrate to secondary lymphoid tissue. We show that purified blood mDC cultured in vitro with GM-CSF and IL-4, but in the absence of added exogenous maturation stimuli, rapidly differentiate into two maturational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
6
27
0
Order By: Relevance
“…Low levels of activin-A were detected by 4 hours after stimulation reaching by 24 hours to between 0.4 and 1 ng/mL ( Figure 2D). Consistent with the fact that these cells spontaneously mature on in vitro culture 50 (and our unpublished data), it was found that unstimulated CD1c ϩ PBDCs produced equivalent levels of activin-A to those detected after stimulation with the various classes of stimuli tested ( Figure 2D). Furthermore, CD1c ϩ PBDCs produced similar levels of activin-A (with or without stimuli) irrespective of culture in serum-containing or serum-free media ( Figure 2E).…”
Section: Blood DC Subsets But Not Other Immune Cells In Human Bloodsupporting
confidence: 86%
“…Low levels of activin-A were detected by 4 hours after stimulation reaching by 24 hours to between 0.4 and 1 ng/mL ( Figure 2D). Consistent with the fact that these cells spontaneously mature on in vitro culture 50 (and our unpublished data), it was found that unstimulated CD1c ϩ PBDCs produced equivalent levels of activin-A to those detected after stimulation with the various classes of stimuli tested ( Figure 2D). Furthermore, CD1c ϩ PBDCs produced similar levels of activin-A (with or without stimuli) irrespective of culture in serum-containing or serum-free media ( Figure 2E).…”
Section: Blood DC Subsets But Not Other Immune Cells In Human Bloodsupporting
confidence: 86%
“…Our previous studies have shown that after culture for 2 days in the presence of GM-CSF and IL-4, blood mDC differentiate and acquire markers such as CD1a and DC-SIGN, characteristic of tissue DC [24]. Transduction of 48 h cultured mDC led to higher levels of eGFP expression, with and without CD40L stimulation, than freshly isolated cells for all three vectors.…”
Section: Myeloid DCmentioning
confidence: 84%
“…In this regard, CD1c ϩ DCs rapidly and spontaneously mature in vitro. 44 As a result, CD1c ϩ DCs may lose the capacity to internalize and process antigen compared with MoDCs. The combined effects of reduced antigen uptake capacity and limiting intracellular colocalization of antigen and adjuvant may explain the differing efficiencies of cross-presentation between these 2 DC subsets.…”
Section: Discussionmentioning
confidence: 99%